Electrical steels for rotating machines - Beckley, P. (Institution of Engineering and Technology, 2002)
There are 15 chapters in the book. The following topics are dealt with: electrical steel manufacturing method; coatings; insulation; punching effects; core building; high-frequency applications; finite element design method; magnetic testing; magnetic property measurement; costing; quality management; thickness assessment; standards; and annealed steels.
Keywords: Steel, Electrical.; Electric machinery.; elektronické knihy; electronic books